Chemosynthetic ethanolamine plasmalogen stimulates gonadotropin secretion from bovine gonadotrophs by acting as a potential GPR61 agonist - Kadokawa, Hiroya; Yoshino, Ryunosuke; Saito, Risa; Hirokawa, Takatsugu (Animal reproduction science, 2022)
Brain ethanolamine plasmalogens (EPls) are unique alkenylacyl-glycerophospholipids and the only recognized ligands of G-protein-coupled receptor 61 (GPR61), a newly identified receptor that colocalizes with GnRH receptors on gonadotrophs. As the chemical synthesis of EPl is challenging, only one chemosynthetic EPl, 1-(1Z-octadecenyl)− 2-oleoyl-sn-glycero-3-phosphoethanolamine (PLAPE; C18:0-C18:1), is commercially available. Therefore, we tested the hypothesis that PLAPE stimulates gonadotropin secretion from bovine gonadotrophs. We prepared anterior pituitary cells from healthy, post-pubertal heifers, cultured for 3.5 d, and then treated them with increasing concentrations (0, 0.5, 5, 50, or 500 pg/mL) of PLAPE for 5 mi, before either no treatment or GnRH stimulation. After 2 h, medium samples were harvested for FSH and LH assays. PLAPE (5–500 pg/mL) stimulated (P < 0.01) basal FSH and LH secretion, and such stimulation effects were inhibited by a SMAD pathway inhibitor. In the presence of GnRH, PLAPE at 0.5 and 5 pg/mL stimulated FSH and LH secretion (P < 0.01). However, a higher dose of PLAPE (500 pg/mL) suppressed GnRH-induced FSH and LH, and such suppressive effects were inhibited by an ERK pathway inhibitor. PLAPE stimulated gonadotropin secretion in the presence of EPls extracted from the brains of young heifers, but not old cows. Additionally, we performed in silico molecular-docking simulations using the deep-learning algorithm, AlphaFold2. The simulations revealed the presence of three binding sites for PLAPE in the three-dimensional structural model of GPR61. In conclusion, PLAPE stimulated gonadotropin secretion from bovine gonadotrophs and might act as a chemosynthetic agonist of GPR61. [Display omitted] •PLAPE stimulated basal FSH and LH secretion from bovine anterior pituitary cells.•High, but not low, doses of PLAPE suppressed GnRH-induced FSH and LH secretion.•SMAD pathway inhibition suppressed PLAPE-induced FSH and LH secretion.•ERK pathway blocked the high PLAPE-induced suppression of GnRH-stimulated secretion.•An in silico simulation clarified three binding sites for PLAPE in a 3D GPR61 model.